2008
DOI: 10.1016/j.jcmg.2008.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Magnetic Resonance Characterization of Mitral Valve Prolapse

Abstract: Cardiovascular magnetic resonance image can identify MVP by the same echocardiographic criteria and can identify myocardial fibrosis involving the papillary muscle in MVP patients. Hyperenhancement of papillary muscles on LGE is often present in a subgroup of patients with complex ventricular arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
156
2
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(171 citation statements)
references
References 35 publications
8
156
2
5
Order By: Relevance
“…Thus, a regional LV papillary muscle and inferobasal fibrosis was found to characterize both MVP victims with SCD as well as MVP patients with complex ventricular ectopy; presenting a novel specific risk factor for SCD among MVP patients. Notably, similar findings on CMR or histopathology have been previously reported [12,13]. Given the correlation between the source of ventricular ectopy and the areas of cardiac fibrosis, a mechanical stretch hypothesis has been raised [14], by which a mechanical stretch of the myocardium in these specific areas results from the prolapsing MV leaflets.…”
supporting
confidence: 64%
“…Thus, a regional LV papillary muscle and inferobasal fibrosis was found to characterize both MVP victims with SCD as well as MVP patients with complex ventricular ectopy; presenting a novel specific risk factor for SCD among MVP patients. Notably, similar findings on CMR or histopathology have been previously reported [12,13]. Given the correlation between the source of ventricular ectopy and the areas of cardiac fibrosis, a mechanical stretch hypothesis has been raised [14], by which a mechanical stretch of the myocardium in these specific areas results from the prolapsing MV leaflets.…”
supporting
confidence: 64%
“…Хотя изменения систолической и диастолической функций может быть обусловлено развитием фиброза миокарда ЛЖ, появление которого, как мы уже отме-чали, недавно было описано у симптомных пациентов с ПМК при проведении магнитно-резонансной томо-графии [24] у бессимптомных лиц молодого возраста, наиболее вероятной причиной выявленных нами изменений регионарной сократимости является нару-шение структуры и функции соединительной ткани.…”
Section: Discussionunclassified
“…Localization of valve dysfunction is important for surgical planning, as some mitral valve abnormalities are less amenable to successful mitral valve repair (e.g., repair is less durable for extensive anterior leaflet disease) (42). Among a cohort of 25 patients with MVP, Han et al reported cine-CMR assessment of leaflet displacement to provide high sensitivity (100%) and specificity (100%) compared to the reference standard of transthoracic echo (43). Among a cohort of 27 patients with MVP, Gabriel et al reported that cine-CMR accurately determined presence or absence of involvement of each leaflet in 98% of cases compared to the reference of transthoracic echo; in a subset of patients (n=10) who underwent transesophageal echo or surgery, accuracy of cine-CMR was 82% (44).…”
Section: Primary Mrmentioning
confidence: 99%
“…Beyond mitral valve structure and function, CMR can be used to assess altered myocardial tissue properties associated with MVP. For example, Han et al used DE-CMR to assess papillary muscle fibrosis among a pilot cohort of 16 patients with MVP (43). The authors reported papillary fibrosis to be present in over half (10/16) patients with MVP in whom it was associated with increased ventricular ectopy, suggesting that this finding may be of prognostic significance (43).…”
Section: Primary Mrmentioning
confidence: 99%
See 1 more Smart Citation